Application of transesophageal echocardiography, left atrial appendage angiography, cardiac computed tomography angiography, and three-dimensional reconstruction model in left atrial appendage occlusion - Huang Hao Lei; Li Hua Kang; Song Zhi Yuan; Wan Chen; Yao Qing (International Journal of Distributed Sensor Networks)
Objective: The objective was to evaluate the application of transesophageal echocardiography, left atrial appendage angiography, cardiac computed tomography angiography, and three-dimensional reconstruction model in the left atrial appendage occlusion. Methods: A total of 53 patients with persistent atrial fibrillation hospitalized from January 2015 to February 2019 were selected. Transesophageal echocardiography and cardiac computed tomography angiography were performed simultaneously before operation, and three-dimensional reconstruction of the left atrial appendage model was performed based on the cardiac computed tomography angiography findings. The morphology and size of the left atrial appendage were displayed by the left atrial appendage angiography during the operation. Results: Cardiac computed tomography angiography revealed filling defects in the left atrial appendage in four patients, whereas transesophageal echocardiography revealed thrombosis in two patients of the four patients. According to the cardiac computed tomography angiography results, the morphology of the left atrial appendage was classified into chicken wing–like, cauliflower-like, wind vane–like, and cactus-like. The diameters and depths of the left atrial appendage measured by cardiac computed tomography angiography and three-dimensional reconstruction model were found to be the greatest, and the orifice sizes and depths of the left atrial appendage measured by the left atrial appendage angiography were the smallest. Conclusion: Transesophageal echocardiography, left atrial appendage angiography, cardiac computed tomography angiography, and three-dimensional reconstruction model can evaluate the morphology and size of the left atrial appendage. The cardiac computed tomography angiography and three-dimensional reconstruction model could demonstrate the internal structure of the left atrial appendage more clearly.